International Conference on Advancements of Medicine and Health Care through Technology 29th August - 2nd September 2011, Cluj-Napoca, Romania - Vlad, Simona; Ciupa, Radu V. (Springer, 2011)
This volume presents the contributions of the third International Conference on Advancements of Medicine and Health Care through Technology (Meditech 2011), held in in Cluj-Napoca, Romania. The papers of this Proceedings volume present new developments in - Health Care Technology, - Medical Devices, Measurement and Instrumentation, - Medical Imaging, Image and Signal Processing, - Modeling and Simulation, - Molecular Bioengineering, - Biomechanics.